a+b+c+d = 720
a+5=b-5=c:5=d*5
Le scriem pe toate funcție de a.
a+5=b-5 => b=a+5+5 => b=a+10
a+5=c:5=> c= (a+5) *5 => c=5a+25
a+5=d*5 => d=(a+5):5
și înlocuim în sumă: a+b+c+d=720 => a+ a+10+ 5a +25 + (a+5):5 = 720 =>
7a + 35 + (a+5):5 = 720 => (a+5):5 = 720-35-7a => (a+5):5 = 685-7a => a+5 = (685-7a)*5 => a+5 = 3425 - 35a => 36a = 3420 => a= 3420:36 => a=95
Acum înlocuim a în expresiile de mai sus pentru b, c și d
b= a+10 => b= 95+10 => b=105
c=5a+25 => c=5*95+25 => c=500
d=(a+5):5 => d=(95+5):5 => d=20